Black Internationalism's Shifting Alliances: African American Newspapers, the White Australia Policy, and Indigenous Australians, 1919–1948 - Corbould, Clare (History compass, 2017)
African American newspapers frequently ran reports and stories about Indigenous Australians and Australia's racial governance between 1919 and 1948, except for the years during World War II when thousands of African American servicemen were stationed in Australia. The black American press was extremely critical of "White Australia." African American newspaper writers used the phrase "White Australia" to refer both to the famed or notorious Australian immigration laws and to prevailing race relations in labor management. When they reported on Indigenous Australians, they took careful note of conditions that were akin to American slavery and its aftermath and remarked upon the similar regimes of racial governance. As far as the black American press was concerned, Indigenous Australians were one of the many nodes that comprised a worldwide alliance of colonized people; black internationalism included them, too. From 1942 to 1944, however, the press placed that alliance on hold. Newspapers instead focused on the surprisingly benign treatment they said black American troops received from white Australians. As it became clear that the Allies were likely to triumph, black American newspapers returned to criticism of "White Australia" and to an abstract bond with Aboriginal Australians, as they pressed forward with claims to universal human rights and with agitation to end all colonization as part of the worldwide return to peace.